Is stockperson welfare essential for animal welfare? - Vicentini, Fernanda Victor Rodrigues Vieira; Amorim Franchi, Guilherme; da Silva, Iran José Oliveira (Revista de Ciências Agroveterinárias, 2017)
Increasingly, animal welfare (AW) is gaining ground worldwide because of pressure from importing countries, as well as the demand from a more conscious society regarding the living conditions of farm animals. Despite the growing concern about AW, there are few studies of stock person’s welfare and how it might influence AW. The treatment of animals connects to stockpersons’ attitudes and behaviour, which in turn are associated with several human factors such as initial experience in the activity, welfare, quality of working conditions and human-animal relationship. Many authors have investigated this relationship and its association with positive attitudes of stock persons towards animals, which consequently influence AW and productivity. However, currently, there is no highlighted concern about the human issue, as the stock person welfare (SW), believed to be a key aspect of a successful implementation of AW programs. The present work suggests a broader view concerning AW, its relation to SW and the importance of improving both aspects in livestock systems.